Roles of the Cannabinoid System in the Basal Ganglia in Parkinson’s Disease - Wang, Mengya; Liu, Huayuan; Ma, Zegang (Frontiers in Cellular Neuroscience, 2022)
Parkinson’s disease (PD) is a neurodegenerative disease usually caused by neuroinflammation, oxidative stress and other etiologies. Recent studies have found that the cannabinoid system present in the basal ganglia has a strong influence on the progression of PD. Altering the cannabinoid receptor activation status by modulating endogenous cannabinoid (eCB) levels can exert an anti-movement disorder effect. Therefore, the development of drugs that modulate the endocannabinoid system may be a novel strategy for the treatment of PD. However, eCB regulation is complex, with diverse cannabinoid receptor functions and the presence of dopaminergic, glutamatergic, and γ-aminobutyric signals interacting with cannabinoid signaling in the basal ganglia region. Therefore, the study of eCB system is challenging. Here, we have described the function of the cannabinoid system in the basal ganglia and its association with PD in three parts (eCBs, cannabinoid receptors, and factors regulating the cannabinoid metabolism) and summarized the mechanisms of action related to the cannabinoid analogs currently aimed at treating PD. The shortcomings identified from previous studies and the directions that should be explored in the future will provide insights into new approaches and ideas for the future development of cannabinoid-based drugs and the treatment of PD.